Displaying Disability: A Content Analysis of Person-First Language on NCAA Bowl Championship Series College Athletic Department Websites - Joshua R. Pate; Brody J. Ruihley; Timothy Mirabito (Journal of Applied Sports Management, 2014)
The purpose of this study was to (a) explore how information on accessible seating and parking was presented on college athletic department websites, and (b) identify what language was being used on college athletic department websites to communicate to people with disabilities. A content analysis was conducted with 67 NCAA Bowl Championship Series college athletic department websites. Results indicated that no more than 56.7% of schools used person-first language in reference to accessible seating and parking. Less than 36% of schools used person-first language in accessible parking headings or text, revealing a discrepancy in seating and parking language. The difference indicates that athletic department personnel are not familiar with the preferences of most people with disabilities. Athletic department personnel should ensure they are using person-first language to avoid offending a segment of their stakeholders and to foster relationships with a brand-loyal group of potential season ticket holders.
Keywords: college athletics; disability; NCAA; stakeholders; website